Alternatif modernleşme ve üçüncü sinema - Güldoğan, Mehmet (My University, 2010)
İki kutuplu dünyanın sona ermesiyle başlayan yeni dünya siyasasının, dünyanın birçok coğrafyasında görülen etkileri Türkiye’ye de ulaşmış; son yıllarda yaşanan iktisadi-sosyo-kültürel değişimler Türkiye’nin alt ve üst yapılarında köklü değişimleri meydana getirmiştir. Bu değişiminin bir etkisi olarak, cumhuriyetin kuruluşundan günümüze kadar geçerliliğini sürdüren ulus-devlet anlayışı, bugün ülke gündeminde sıkça rastladığımız üzere, köklü bir değişim sürecine girmiştir Türkiye’de. Bu çalışma, yaklaşık üç yüzyıllık bir süreç içinde toplumsal kurtuluş projesinden büyük toplumsal yıkımlara doğru evrilen, aklın araçsallaştığı modern tarihe göz atarken, diğer yandan geri kalmış ulusların aydınlanma mücadelesinde dikkate değer bir adım olan Üçüncü Sinema’yı ele almaktadır. Ülkemizde de ürünler vermiş Üçüncü Sinema’nın gelişim seyri, Türkiye’de ve dünyada süregiden egemenlik ilişkilerine ve buna karşı geliştirilen muhalefetin karakterine ilişkin ipuçları sunması açısından önemlidir. Name and Surname : Mehmet Güldoğan Field : Radio, Television and Cinema Programme : Cinema Supervisor : Yrd. Doç. Dr. Göksel Aymaz Degree Awarded and Date : Master – December 2010

After the end of the bipolar world, the effects of the new world politics was seen in many parts of the world and these effects have also reached to Turkey. The socio-economic-cultural changes that have been experienced in recent years gave rise to profound changes in Turkey’s lower and upper structures. As the effect of these changes, the concept of the nation-state that is valid from the establishment of republic to the present has entered into a long process of change in Turkey as today we have met frequently on the agenda for the country. This study considers both as within a period of three centuries evolving social liberation project into major social degradation, and looking into the modern history of instrumentalisation mind and as Third Cinema which is a remarkable step in the underdeveloped nations’ struggle for enlightenment. The development process of Third Cinema that has given products in our country is significant to provide clues about in terms of continuing sovereignty relations in Turkey and the world, and to be developed character of oppositional against it.
Keywords: Beyaz Perde; Modernleşme; Sinema